2019
DOI: 10.1002/jsfa.9668
|View full text |Cite
|
Sign up to set email alerts
|

Identification of geographical origin of Keemun black tea based on its volatile composition coupled with multivariate statistical analyses

Abstract: BACKGROUND: Keemun black tea (KBT) is one of the most popular tea beverages in China as a result of its unique flavor and potential health benefits. The geographical origin of KBT influences its quality and price. The present study aimed to apply a head-space solid phase microextraction approach and gas chromatography-mass spectrometry combined with chemometric analysis to profile the volatile compounds of KBT collected from five production areas.RESULTS: Thirty-one peaks were detected in 61 KBT samples. Hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
1
18
1
Order By: Relevance
“…Limonene and β-myrcene were the most important volatile components in orange ( Citrus sinensis ), lemon ( Citrus limon ), and mandarin ( Citrus reticulata ), and a very low content had also been identified in pure tea [ 12 , 13 , 19 , 20 ]. Compared with the previous report in lemon and tea, p -Cymene was much higher in our results [ 7 , 13 , 18 , 21 ]. It was supposed that p -cymene and linalool may come from both citrus and tea leaves.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Limonene and β-myrcene were the most important volatile components in orange ( Citrus sinensis ), lemon ( Citrus limon ), and mandarin ( Citrus reticulata ), and a very low content had also been identified in pure tea [ 12 , 13 , 19 , 20 ]. Compared with the previous report in lemon and tea, p -Cymene was much higher in our results [ 7 , 13 , 18 , 21 ]. It was supposed that p -cymene and linalool may come from both citrus and tea leaves.…”
Section: Discussioncontrasting
confidence: 93%
“…In detail, limonene was absolutely the highest constituent (CG, 35.41%; BG, 26.10%; LG, 29.44%), followed by β-myrcene (CG, 4.75%; BG, 5.73%; LG, 4.25%). Benzaldehyde was the main aldehyde, which was reported in many famous Chinese black teas, and considered as a key aroma compound in them contributing floral odorant [ 17 , 18 ]. p -Cymene, a common aromatic hydrocarbon in nature, with various biological activities, was detected in a high level (CG, 2.82%; BG, 6.93%; LG, 5.80%).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the differences of region conditions including temperature, precipitation and altitude (Fang et al., 2017; Liang et al., 2008), previous studies showed the differential compounds contributed to the identification of geographical origin (Fang, Huang et al., 2019; Fang, Ning et al., 2019; Xin et al., 2018). Based on the differential metabolites related to production place (Supporting information Table S1) and tea cultivar (Supporting information Table S2), KEGG metabolic pathway analysis was carried out with Arabidopsis thaliana as the corresponding species (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic sensory and the nutritional properties of KBT vary slightly depending on its geographical origin . There are several famous tea subregions in China such as Longjing Village, Anxi Town, Qimen Town, and Dongting Mountain, and tea cultivation areas with long history .…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic sensory and the nutritional properties of KBT vary slightly depending on its geographical origin. 2 There are several famous tea subregions in China such as Longjing Village, Anxi Town, Qimen Town, and Dongting Mountain, and tea cultivation areas with long history. 3,4 As the price of KBT from Qimen Town is much higher than other black teas from adjacent regions (such as Guichi and Dongzhi County), many imitation products have existed in almost all tea-production areas in Anhui Province in recent years, causing confusion in the tea market.…”
Section: Introductionmentioning
confidence: 99%